Copepods as Indicators of Different Water Masses during the Northeast Monsoon Prevailing Period in the Northeast Taiwan - Yan-Guo Wang; Li-Chun Tseng; Rou-Xin Sun; Xiao-Yin Chen; Peng Xiang; Chun-Guang Wang; Bing-Peng Xing; Jiang-Shiou Hwang (Biology, 2022)
During this research, the average surface temperature, salinity, dissolved oxygen, and pH were 24.65 ± 1.53 (°C), 34.21 ± 0.07 (PSU), 6.85 ± 0.18 (mg/L), and 8.36 ± 0.03, respectively. Based on these environmental parameters, stations were arranged into three groups. Group A represents stations located around Keelung Island with the relative highest average dissolved oxygen, lowest average temperature, and pH values. Instead, the lowest average dissolved oxygen and highest average temperature, salinity, and pH values were recorded at the offshore stations. Keelung Island area was charged by cold water masses, which were driven by the Northeast monsoon, and stations in group C were affected by the Kuroshio Current. Kueishan Island area was mainly affected by mixed water masses resulting from the Kuroshio intrusion and monsoon-derived cold water. In this study, a total of 108 copepod species were identified, with an average abundance of 774.24 ± 289.42 (inds. m−3). Most species belong to the orders Calanoida and Poecilostomatoida, with an average relative abundance (RA) of 62.96% and 30.56%, respectively. Calanoid copepodites were the most dominant group, with a RA of 28.06%. This was followed by Paracalanus aculeatus, with a RA of 18.44%. The RA of Clausocalanus furcatus and Canthocalanus pauper was 4.80% and 3.59%, respectively. The dominant species P. aculeatus, C. pauper, Paracalanus parvus, and Temora turbinata were positively correlated with dissolved oxygen and negatively correlated with temperature in the surface waters. pH showed a negative correlation with P. parvus and T. turbinata, while the temperature was negatively correlated with these two dominant species. Indicator species were selected by an indicator value higher than 50%. Temora turbinata, Calanopia elliptica, C. pauper, Euchaeta concinna, Temora discaudata, Acartia pacifica, Macrosetella gracilis, Corycaeus speciosus, and P. parvus were considered as monsoonal cold water indicator species in Group A. Indicator copepod species for the Kuroshio Current were Farranula concinna, Copilia mirabilis, Candacia aethiopica, Corycaeus agilis, Farranula gibbula and Acrocalanus monachus in the study area. Paracandacia truncata, Oncaea clevei, P. aculeatus, and Centropages furcatus were considered suitable indicators for mixed water masses.